PEMBERIAN WASIAT WAJIBAH TERHADAP AHLI WARIS BEDA AGAMA - Muhammad Rinaldi Arif (Universitas Muhammadiyah Sumatera Utara, 2017)
According to Islamic law, one of the obstacles to get inheritance is the religious difference between joint heirs and testator. The condition for the joint heirs of different religions felt unfair, so the problem is then brought to the realm of law. The Supreme Court Decision Number 368.K/AG/1995 provides a way for the joint heirs of different religions to obtain the inheritance through a wasiat wajibah. This study is a descriptive analysis that leads to normative legal research, with a research of legal approach. Data collection is obtained from secondary data by library study. The data obtained is then analyzed using qualitative analysis. Based on the results of the research according to the Supreme Court Decision Number 368.K/AG/1995, the concept of wills is not only for adopted children or adoptive parents, but also for non-Muslim heirs by giving Part or portion of the heirs of different religions based on the heirs of different religions based when he/she is Muslim. Analysis of the Decision of the Supreme Court of the Republic of Indonesia Number 368.K/AG/1995, about the provision of wasiat wajibah to the heirs of different religions is that the provision of wasiat wajibah to the heirs of non-Muslims actually is not in accordance with the rules of Islamic law.